1999
DOI: 10.1017/s0021963098003618
|View full text |Cite
|
Sign up to set email alerts
|

Quebec Child Mental Health Survey: Prevalence of DSM-III-R Mental Health Disorders

Abstract: The Quebec Child Mental Health Survey (QCMHS) was conducted in 1992 on a representative sample of 2400 children and adolescents aged 6 to 14 years from throughout Quebec. Prevalences of nine Axis-I DSM-III-R (American Psychiatric Association, 1987) mental health disorders were calculated based on each informant (for 6-11-year-olds: child, parent, and teacher; for 12-14-year-olds: child and parent). Informant parallelism allows the classification of results of the demographic variables associated with disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
0
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 78 publications
(109 citation statements)
references
References 10 publications
5
94
0
10
Order By: Relevance
“…In Spain, prevalence rates 14.4%, 5.3% and 3.0% were reported for three separate samples of children aged 8, 11 and 15 years, respectively [26]. Similar findings were reported in Canada, with prevalence rates of 5.5%, 4.0%, and 2.5% for children aged 6-8, 9-11, and 12-14 years, respectively [10], and in the USA, with prevalence rates 18.2%, 15.9% and 14.8% for children aged 3-5, 5-12 and 12-18 years, respectively [40].…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…In Spain, prevalence rates 14.4%, 5.3% and 3.0% were reported for three separate samples of children aged 8, 11 and 15 years, respectively [26]. Similar findings were reported in Canada, with prevalence rates of 5.5%, 4.0%, and 2.5% for children aged 6-8, 9-11, and 12-14 years, respectively [10], and in the USA, with prevalence rates 18.2%, 15.9% and 14.8% for children aged 3-5, 5-12 and 12-18 years, respectively [40].…”
Section: Resultssupporting
confidence: 76%
“…Higher prevalence rates have been associated with lower socioeconomic status [23,27,33,42,51] and among urban as compared to rural residence [6], but no significant differences were observed regarding the place of residence in other studies [10,14,32,40,49]. Prevalence variations between different racial and ethnic groups have not been adequately examined.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Caveats in these earlier studies included problems with sampling, case definitions, data analysis, and presentation [14]. Since 1990, impairment criteria have been included in prevalence studies such as the Quebec Child Mental Health Survey (using DISC and both parents and teachers as informants) [15] and the Great Smoky Mountains Study [16] (using the Child and Adolescent Psychiatric Assessment, or CAPA, interview and the Children's Global Assessment Scale, or C-GAS, as a measure of impairment) [17]. Three reviews of studies done in the past four decades found prevalence rates of 5-22% for psychiatric disorders among children and adolescents [7,11,14].…”
Section: Introductionmentioning
confidence: 99%